Metabolomics and Metabolic Pathway Analysis: Decoding Cellular Biochemistry - Ale, Ebenezer Morayo; Akinseye, Olanrewaju Roland; Boyi, Richard-Harris Nsenreuti; Ayo, Victoria Ifeoluwa; Timothy, Mgbede Joy; Asuelimen, Steve Osagie (Innovations in Biological Science Vol. 6, 2024)
Metabolomics is the systematic study of small molecule metabolites found within cells, tissues, or biofluids. It aims to provide a functional readout of biochemical activities and hence can provide an integrated view of the biochemical status of living systems. Metabolomic studies have been used to better understand various disease states, identify biomarkers, and study the effects of drug treatments or toxic exposures. This chapter will introduce the concepts and technologies behind metabolomics experiments including mass spectrometry and nuclear magnetic resonance spectroscopy. Methods for metabolite identification, quantification and data analysis will be discussed. A key application of metabolomics data is in mapping metabolites to biochemical pathways and constructing metabolic networks. Various bioinformatics resources for pathway mapping and analysis will be presented such as KEGG, Reactome and WikiPathways. Computational approaches for metabolic modeling and simulation will also be covered. Case studies demonstrating how integrated metabolomic and pathway analysis has provided novel insights into cancer metabolism, drug toxicity and personalized medicine will be reviewed. The chapter will conclude by discussing current challenges and future opportunities in metabolomics and metabolic pathway analysis, such as integrating ‘omics data and applying network-based approaches for systems-level understanding of metabolism.